CHARACTERISTICS OF SMOKED CATFISH (Hemibagrus nemurus) PREPARED FROMPOND CULTURE, CAGE AND WILD FISH - Maskilin, Jippo; Hasan, Bustari; Leksono, Tjipto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study was aimed to evaluate the sensory quality, proximate composition, amino acids and fatty acids profiles of smoked catfish prepared from pond, cage culture and wild fish. Catfish samples 300-350 grams in weight wastaken respectualy from wild (Kampar river), pond and cage culture in Sungai Paku, Kampar. The fish was smoked using hot smoking method, and the smoked fish was evaluated for smoking yield, sensory quality, proximate composition, amino acid and fatty acid profile.The smoking yield value for smoked fish prepared from pond culture fish was the highest, and then followed by that prepared from cage culture fish and wild fish. The highest fat and moisture composition was found in smoked fish prepared from pond culture fish, then followed by cage culture fish and wild fish. Protein and ash was the highest in smoked fish prepared from wild fish then followed by cage and pond culture fish. Overally, sensory quality and essential amino acid profile of smoked fish was not much different among the fish from different sourcer. However, PUFA was the highest in the smoked fish prepared from cage culture fish them followed by wild fish and pond fish.Keywords: Hemibagrus nemurus,smoked fish,smokingyield, Sensory quality, proximate composition, fatty acid, amino acid